A CRITICAL APPRAISAL OF ACTUALIZING THE VISION OF LUMEN GENTIUM - Cruz, Nathaniel (Asian Horizons, 2013)
The Second Vatican Council opened up many discussions especially on the Church. The last 51 years, since the Council began, have seen various developments in the self-understanding of the Church. In the last century, in understanding the Church, emphases have passed from understanding her as Societas Perfectas, to the Mystical Body of Christ, and from the Church as ‘People of God’ to the Church as ‘communion.’ Now the problem of actualising the vision of the Second Vatican Council is well expressed by one of the Fathers of the Council himself, Pope Benedict XVI, in 2005 as a problem of the “correct interpretation” of the Council or its “proper hermeneutics.”1 In front of the many discussions the Dogmatic Constitution of the Second Vatican Council has opened up, in the following paragraphs some possible perplexities in understanding the Church are highlighted.